(untitled) (Horizontes de Enfermería, 2018)
By providing complete information on the objectives, goals, strategies National Immunization (ENI) by localities at national level the implementation of ENI in the population of the province of Carchi - Canton San Pedro de Huaca and Tulcán in children under 1 year - from 12 to 24 months, immunization is guaranteed in this population and equity, through free quality vaccines that satisfy the user, based on effective and effective epidemiological management and surveillance at all levels of management, During the year 2017 of January-August, coverage has been achieved above 50% of vaccination with a complete scheme, fulfilling the primary objective of the National Immunization (ENI) strategies to eradicate six priority diseases: tuberculosis (severe forms), poliomyelitis , diphtheria, whooping cough or pertussis, tetanus and measles, establishing strategies to strengthen and increase the uptake of children under two years, guaranteeing the coverage of vaccines with complete scheme in this population. Among the indicators of strategic and operational performance analysis established by the national immunization control, the coverage of Rotavirus vaccines (second dose), and Pentavalent (third dose), obtained in August 89.16% and 89.24% respectively.